Emerging cell cycle inhibitors for treating metastatic castration-resistant prostate cancer. (2nd October 2018) - Batra, Anupam; Winquist, Eric
ABSTRACT: Introduction : Disease progression despite androgen suppression defines lethal castration-resistant prostate cancer (CRPC). Most of these cancers remain androgen receptor (AR)-signaling dependent. Therapy for metastatic CRPC includes abiraterone acetate, enzalutamide, docetaxel, cabazitaxel, sipuleucel-T, and radium-223. However, survival remains modest for men with progressive disease despite AR-targeted therapy and docetaxel, and therefore novel treatments are needed. Areas covered : Recent evidence of genomic heterogeneity and sensitivity to PARP inhibitors supports investigation of targeted agents in CRPC. Cell cycle inhibitors are therefore logical molecules to investigate. Review of the current literature identified cell cycle inhibitors under study in early phase clinical trials targeting the G1 (palbociclib, ribociclib, AZD-5363, ipatasertib), S (M-6620, prexasertib), G2 (adavosertib), and M (alisertib) phases of the cell cycle. Expert opinion : Strategies combining cell cycle inhibitors with active agents in CRPC are most likely to have clinical impact with CDK4/6 and Wee1 inhibitors appearing most promising. Identification of predictive biomarkers may be essential and currently trials are testing circulating cell-free DNA as an approach. Incremental toxicities such as neutropenia are important in this population. Results from most current clinical trials of cell cycle inhibitors in CRPC are still pending but it is anticipated they will provide important insights into the heterogeneous biology of CRPC.